INDONESIAN STUDENTS MISCONCEPTION IN USING PRESENT PERFECT TENSE TO WRITE COMPOSITION - Syaifur Rochman (Soegijapranata Catholic University, 2003)
This article describes a research on the error analysis in the uses of present peifect tense made by freshmen studying at English Department in